Impact of universal vaccination with pneumococcal conjugate vaccine on invasive pneumococcal disease in a private general hospital in a the Southern Cone of Latin America country (Archives of Pediatrics of Uruguay, 2025)
Introduction: in 2008, a country in the Southern Cone of Latin America implemented universal childhood vaccination with the 7-valent pneumococcal conjugate vaccine (PCV), later replaced by PCV13 in 2010. Vaccine coverage was over 92%. Since 2004, the pneumococcal polysaccharide vaccine (PPSV23) has been recommended for at-risk adults, and since 2015, PCV13 plus PPSV23 for those at very high risk.Objectives: assess the impact of the universal vaccination strategy on hospitalizations due to invasive pneumococcal disease (IPD) in children and adults in a private general hospital.Methodology: a descriptive and retrospective study conducted in a private tertiary general hospital. It included children and adults hospitalized with a diagnosis of IPD during the period 1/1/2006 to 31/12/232023. Three study periods were established: prior to PCV implementation (2006 to 2007), early post-implementation (2009 to 2015), and late post-implementation (2016 to 2023). Hospitalization rates, disease type, proportion of vaccine and non-vaccine pneumococcal serotypes, and case-fatality and mortality rates were calculated and compared. Categorical variables were described as numbers and percentages. Continuous variables were described as median and range. It was approved by the institutional ethics committee. The degree of univariate association was examined using the Mid-P exact test, Student’s t-test, and Chi-square test, as appropriate. A p-value
Keywords: Pneumococcal Vaccine; Pneumococcal Infection